MAGNESIOHÖGBOMITE (MG,FE2+,ZN)8 (AL,TI,FE3+)20O38(OH)2 FROM ILMENOGORSKY-VISHNEVOGORSKY COMPLEX - V.G. Korinevsky; V.A. Kotlyarov; E.V. Korinevsky; A.B. Mironov; M.V. Shtenberg (Минералогия)
Rare mineral magnesiohögbomite was found in spinel-sapphirine hornblendites and titanomagnetite clinopyroxenites, which compose the large blocks in tectonic sheets of serpentinites among gneisses of the Kyshtym sequence (Ilmenogosrky-Vyshnevogorsky complex, South Urals). In hornblendite, magnesiohögbomite occurs as grains 0.02–0.6 mm in size. It is characterized by the low iron mole fraction (f = 0.34–0.49) and contains 6–7 wt. % TiO2 and up to 0.25 wt. % Cr2 O3 . In clinopyroxenite, magnesiohögbomite forms black (brown at the edges) platy grains 0.3–0.8 mm (up to 1–7 mm) across with pitch luster and conchoidal fracture. It contains considerably less TiO2 and more MgO relative to that from hornblendites. The intensive lines of its XRD pattern are (d, Å; I): 4.61 (26), 3.37 (26), 2.867 (27), 2.744 (53), 2.492 (62), 2.433 (100), 2.084 (42), 1.982 (40), 1.573 (29), 1.558 (21), 1.519 (25), 1.443 (53), 1.434 (44). These values reflect hexagonal syngony and indicate the following unit cell parameters of the mineral (Å): a 5.715(5), c 23.931(2), V 677.01(4) Å3 , which can be ascribed to polytype 2N3S.